To treat or not to treat: A rare case of response to pembrolizumab‐based immunotherapy‐chemotherapy in non‐small cell lung cancer with acute liver failure due to multiple bile duct metastases. Issue 4 (27th December 2020) - Shaforostova, Inna; Huss, Sebastian; Gerwing, Mirjam; Evers, Georg; Bleckmann, Annalen
Abstract: About 40% of non‐small lung cancer (NSCLC) patients have metastatic disease at the time of diagnosis. However, metastatic NSCLC in the biliary duct system is extremely rare. A high proportion of patients with acute liver failure due to advanced NSCLC do not receive any treatment due to organ dysfunction or poor performance status. Here, we report a case of successful treatment with chemoimmunotherapy in a young woman with obstructive jaundice and acute hepatic failure due to multiple intrahepatic bile duct metastases. Key points: Significant findings of the study Chemotherapy in NSCLC patients with liver failure is a therapeutic challenge. Acute hepatic failure are often exclusion criteria for therapy of NSCLC. Some reports showed a benefit of ICIs plus chemotherapy for NSCLC with liver metastases. What this study adds Combination of ICIs and chemotherapy is effective and safe in critically ill patients with lung cancer and impaired liver function. Abstract : We report a case of successful treatment with chemimmunotherapy in a young woman with obstructive jaundice and acute hepatic failure due to multiple intrahepatic bile duct metastases of NSCLC.